Proceedings of the 2016 ACM Conference Companion Publication on Designing Interactive Systems 2016
DOI: 10.1145/2908805.2908807
|View full text |Cite
|
Sign up to set email alerts
|

LiveObjects

Abstract: Figure 1: a) LightWire, an illuminated, spinning optic fiber that forms light bodies from social data, b) GorgeBox, an object that inflates based on the accumulation of data, c) LiveFans, two IoT controllable objects that actuate relational data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Torres et al have suggested that there are a lot of possibilities to extend technological artefacts with "unique expressive personalities" that "go beyond neutral, atomic, functional, and obedient "things". A name can help in creating a felt intimacy with devices leading to better experiences through increased "pleasure, social inclusion, and personal value in devices" [26]. The act of changing the point of reference, from 'are you using the drone?'…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Torres et al have suggested that there are a lot of possibilities to extend technological artefacts with "unique expressive personalities" that "go beyond neutral, atomic, functional, and obedient "things". A name can help in creating a felt intimacy with devices leading to better experiences through increased "pleasure, social inclusion, and personal value in devices" [26]. The act of changing the point of reference, from 'are you using the drone?'…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…HCI explores a variety of interactions and fabrication techniques with inflatables. Interaction possibilities with inflatables include punching [27], theatrical data display [40], squeezing a mouse [25], exploring affective qualities of simple movements [37], petting inflatable rabbits [14], bodily compression [15], simulating objects in VR [38], force feedback on the arms in VR [19], or a shoulder "tap" to indicate left or right when giving directions [36]. Fabrication techniques include embroidery with silicone bladders [34], silicone bladders [28], stitching on stretchy fabric to control shape change [39], replay direct manipulation [30], firm 3D printed inflatables [20], rapid prototyping [18], and other shape-changing interfaces [24].…”
Section: Inflatables In Hcimentioning
confidence: 99%